Effects of Fe3+ on Hydrothermal Humification of Agricultural Biomass - Peng, Xiong‐Xin; Gai, Shuang; Liu, Zhuqing; Cheng, Kui; Yang, Fan (ChemSusChem, 2024)
Hydrothermal humification technology for the preparation of artificial humic matters provides a new strategy, greatly promoting the natural maturation process. Iron, as a common metal, is widely used in the conversion of waste biomass; however, the influence of Fe3+ on hydrothermal humification remains unknown. In this study, FeCl3 is used to catalyze the hydrothermal humification of corn straw, and the influence of Fe3+ on the hydrothermal humification is explored by a series of characterization techniques. Results show that Fe3+ as the catalyst can promote the decomposition of corn straw, shorten the reaction time from 24 h to 6 h, and increase the yield from 6.77 % to 14.08 %. However, artificial humic acid (A‐HA) obtained from Fe3+‐catalysis hydrothermal humification contains more unstable carbon and low amount of aromatics, resulting in a significantly decreased stability of the artificial humic acid. These results provide theoretical guidance for regulating the structure and properties of artificial humic acid to meet various maintenance needs. Fe3+‐catalysis hydrothermal humification shortens the reaction time and increases the yield, but the obtained artificial humic acid contains more unstable carbon and lower amount of aromatic compounds, resulting in a significantly decreases stability of the artificial humic acid.